The influence of the sleep disturbances on the quality of patients` life with anxiety-depressive disorders of neurotic and organic genesis - Liashchenko, Yuliia V.; Yuryeva, Lyudmyla M. (Psychiatry, Neurology and Medical Psychology, 2021)
The patients with anxiety-depressive disorders often complain about sleep disturbance. It is due to the high comorbidity of given disorders. They can mutually worsen the duration of each other, complicate the process of treatment and increase the risk of relapse further. Besides, sleep disorders can be preserved even after the compensation of the main disease, that can influence on the quality of life and patient`s social functioning. The goal of the actual research is the learning of the influence of the sleep disorders on the quality of life and patients` social functioning with anxiety-depressive disorders of neurotic and organic genesis. For achievement of the set goal it was explored 120 patients with anxiety-depressive disorders, who were divided into 4 groups depending on the genesis of the disease and the method of medical influence. The research was done with the help of clinic- psychopathology method, adding with Pittsburg index of the quality of the (PSQI), integrative index of the quality of life J Mezzich (the dyad of the patient and the doctor), methods of describing and analytical statistic. As a result of made research, the reverse correlation connections were detected between the sleep disorders and the indexes of the quality of the patient`s life. These connections were observed during the treatment. It was determined, that the combined treatment was the most effective, directed to the therapy of the main disease and directly the correction of the sleep of the patients with anxiety-depressive disorders of neurotic and organic genesis, in comparison with the patients who had a treatment of the main disease. Thus, especial attention must be paid to the correction of insomnia in the treatment of anxiety-depressive disorders with sleep disturbance.